PENERAPAN MODEL PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) PADA SISWA KELAS V SEKOLAH DASAR - Harnika Sari; Yakobus Ason; Burhan . (STKIP Melawi, 2015)
Abstract: The objective of the research is to improve the students' cognitive,affective and psychomotor learning result. The research used Class Action Researchmethod (CAR) which was applied by Kurt Lewin, and consist of 4 stages namely: 1)Planning; 2) Action; 3) Observation; and 4) Reflection. After the action stage iscarried on, the affective aspect viewed from the indicator of attention to the teacher’sexplanation increased by 31.82%; answering questions (Responding) increased by29.55%; responding to teachers and fellow students (Valuing) increased by 27.27%;and 4) discussing and working together between students and teachers (Organization)increased by 29.54%. Observed from the psychomotor aspect, the indicator ofimitating the work/experiment shown by the teacher (Imitation) increased by 18.18%;doing work or trial as directed (Manipulation) increased by 29.54%; doing work orexperiment with precision (Precision) increased by 22,73%; carrying out anexperiment sequentially (Articulation) increased by 25.00%; and habituation ofscientific thinking in doing experiments or other tasks (Naturalization) increased by22.73%. The cognitive aspect viewed from the average score of the learning resulttest obtained by the students on the pre cycle was 36,36, and the first cycle achieved46,36, while the second cycle reached 76,36. Therefore,based on the pre cycle, thepercentage of improvement of learning result after cycle I was 100%. In addition,after the second cycle action, the percentage of the increment in student learningresult also reached 100.00%.Keywords: Interactive Learning Model, Cognitive, Affective, Psychomotor,NaturalScience Learning ResultAbstrak: Tujuan penelitian adalah untuk meningkatkan hasil belajar kognitif, afektifdan psikomotor siswa. Metode penelitian yang digunakan adalah metode penelitiantindakan kelas (PTK) yang diterapkan oleh Kurt Lewin, dengan 4 tahap yaitu: 1)Perencanaan (Plan); 2) Tindakan (Act); 3) Pengamatan (Observe); dan 4) Refleksi(Reflection). Setelah dilakukan tindakan, untuk aspek afektif ditinjau dari indikatormemperhatikan penjelasan guru (Receiving) meningkat sebesar 31,82%; menjawabpertanyaan (Responding) meningkat sebesar 29,55%; memberikan tanggapanterhadap guru dan sesama siswa (Valuing) meningkat sebesar 27,27%; dan 4)berdiskusi dan bekerjasama antara siswa dengan siswa dan siswa dengan guru(Organitation) meningkat sebesar 29,54%. Ditinjau dari aspek psikomotor, indikatormenirukan pekerjaan/percobaan yang ditunjukkan oleh guru (Imitation) meningkatsebesar 18,18%; melakukan kerja atau percobaan sesuai petunjuk (Manipulation)meningkat sebesar 29,54%; melakukan kerja atau percobaan dengan tepat (Precision)meningkat sebesar 22,73%; mengerjakan percobaan sesuai urutan (Articulation)meningkat sebesar 25,00%; dan pembiasaan berpikir ilmiah dalam mengerjakanpercobaan atau tugas lainnya (Naturalization) meningkat sebesar 22,73%. Aspekkognitif dilihat dari rata-rata nilai tes hasil belajar yang diperoleh siswa pada prasiklus 36,36, siklus I sebesar 46,36, dan pada siklus II sebesar 76,36 sehingga dari prasiklus, persentase peningkatan hasil belajar setelah siklus I sebesar 100,00%. Setelahtindakan siklus II, persentase peningkatan hasil belajar siswa juga 100,00%.Kata Kunci: Model Pembelajaran